2009
DOI: 10.15517/rbt.v57i4.5448
|View full text |Cite
|
Sign up to set email alerts
|

El pez Trachelyopterus striatulus (Siluriformes: Auchenipteridae) como herramienta de muestreo de la entomofauna en un embalse tropical

Abstract: The fish Trachelyopterus striatulus (Siluriforms: Auchenipteridae) used to sample insects in a tropical reservoir. The study of aquatic environments is sometimes difficult to do with normal sampling methods that use gears. Insectivorous fishes represent good users of these ecosystems and analyzing the aquatic organisms present in fish stomachs, is an alternative way to determine resource abundance and utilization. In this paper, the potential of Trachelyopterus striatulus as an insect sampler was examined thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
1
1
0
1
Order By: Relevance
“…T. striatulus is also considered omnivorous, encompassing zoobenthos, microcrustaceans, and plants (Silveira et al, 2013). The food preference found for the species in the present study is supported by the findings of Dias et al (2005) and dos Santos et al (2009), who identified insectivorous habits in lotic systems in the southeast region. The presence of a higher percentage of terrestrial—and even some aquatic—insects may be related to the smaller size of the mouth opening, suggesting an adaptation to ingest smaller foods (dos Santos et al, 2015).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…T. striatulus is also considered omnivorous, encompassing zoobenthos, microcrustaceans, and plants (Silveira et al, 2013). The food preference found for the species in the present study is supported by the findings of Dias et al (2005) and dos Santos et al (2009), who identified insectivorous habits in lotic systems in the southeast region. The presence of a higher percentage of terrestrial—and even some aquatic—insects may be related to the smaller size of the mouth opening, suggesting an adaptation to ingest smaller foods (dos Santos et al, 2015).…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, R. quelen has been used as an evaluation tool in various environmental assessments, providing insights into water contaminants (Becker et al, 2009; Ghisi et al, 2011; Marins et al, 2021; Severo et al, 2023). T. striatulus has served as a biodiversity bioindicator for insects and is also associated with the types of exogenous food in water (dos Santos et al, 2009). On the contrary, C. gariepinus is an exotic fish, dominant in many rivers in Africa, and can occupy various trophic levels (Khan et al, 2021; Low et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…No Brasil, Trachelyopterus striatulus ocorre nos rios costeiros, com registros desde o estado da Bahia até o estado de São Paulo (Ferraris Jr., 2003;Montag et al, 2004;Santos et al, 2009;Mesquita et al, 2011;B. Calegari, com.…”
Section: Distribuição Endêmica Do Brasil: Nãounclassified